Analysis of Community Perceptions of Social Welfare in Batam City After the 2019 Presidential Election - Yudhitia Yudhitia; Dhani Akbar; Mahadiansar Mahadiansar (Indonesian Academy of Social and Religious Research (IASRR), 2020)
Social welfare has been a part of the impact of population growth centers in overcoming poverty levels in Indonesia. Community perception is needed as an effort to revive that social welfare is an inseparable part of daily life and is very important in the effort of the government's role in overcoming the disparities that occur given the unstable economic growth in each year. This research was conducted with the aim to analyze people's perceptions of social welfare that occurs in the Batam city community. The method used is survey research in each district in Batam City with descriptive methods that are perceptual sharing of ten categories of assessment, data collected through the distribution of interview questionnaires, observations and supported by secondary data. The focus of this research is on community perceptions of social welfare in Batam City with descriptive qualitative data analysis used to approach that used an average score of interpretation of 0.6 with a scale of 1-4. The results of the analysis show that the indicator of the perception of the people of Batam on social welfare does not have a big impact by the people who only agree to perceive that; (P7) Government programs on social welfare that are right on target felt by the community and (P8) Empowerment of local wisdom / MSMEs that are right on target felt by the community.